2019
DOI: 10.1186/s12884-019-2498-x
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal complications in twin pregnancies in Finland during 1987–2014: a retrospective study

Abstract: Background To investigate the trends and changes in the incidence and overall outcome of twin pregnancies in Finland, a retrospective study was conducted with emphasis on maternal complications, covering a 28-year study period. Methods All 23,498 twin pregnancies with 46,363 live born and 633 stillborn children in Finland during 1987–2014 were included in the study. Data were collected from the national Medical Birth Register and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 27 publications
1
36
1
1
Order By: Relevance
“…The prospective risk of IUFD at ≥34 weeks’ gestation is 0.17% for dichorionic twins 44,45 . There is no significant difference in the risk of stillbirth between dichorionic and monochorionic twins 43,45 . Our analysis indicates that twin pregnancies combining a CHM and a normal fetus both have a very high rate of preterm delivery and IUFD, with only a 50% overall live‐birth rate.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The prospective risk of IUFD at ≥34 weeks’ gestation is 0.17% for dichorionic twins 44,45 . There is no significant difference in the risk of stillbirth between dichorionic and monochorionic twins 43,45 . Our analysis indicates that twin pregnancies combining a CHM and a normal fetus both have a very high rate of preterm delivery and IUFD, with only a 50% overall live‐birth rate.…”
Section: Discussionmentioning
confidence: 68%
“…44,45 There is no significant difference in the risk of stillbirth between dichorionic and monochorionic twins. 43,45 Our analysis indicates that twin pregnancies combining a CHM and a normal fetus both have a very high rate of preterm delivery and IUFD, with only a 50% overall live-birth rate. Pre-eclampsia and chronic vaginal bleeding are probably both major contributors to these perinatal complications.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Moreover, higher levels of chorionic gonadotropin observed in multiple pregnancies predispose to hyperemesis gravidarum, which may be another cause of maternal malnutrition [ 16 , 17 ]. Furthermore, pregnancies with an initially increased risk of numerous complications, including fetal growth disorders, pre-eclampsia, gestational diabetes or preterm labor may also constitute a contributing factor [ 18 , 19 , 20 ]. Therefore, it seems that the supply of nutrients should be properly tailored to the increased needs of a woman to effectively combat all potentially modifiable risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified some errors in Methods, Results and Discussion sections.…”
mentioning
confidence: 99%